Estilo de confrontación y aprovechamiento. Un programa de investigación - Díaz-Guerrero, Rogelio; Peck, Robert F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present paper describes some aspects of the research work that together with seven other countries, Robert F. Peck from the Department of Educational Psychology of the University of Texas, and Rogelio Diaz Guerrero from the Departmento del Ciencias del Comportamiento at the National University of Mexico are carrying out under the title: “Coping Style and Achievement; A Cross-National Study on School Children.” The goal of this study is to identify, and develop ways of measuring styles of coping with work-related problems among children and youth of seven different countries (Italy, Brazil, United States, Mexico, Germany, Japan, England), and sub-cultures thereof. The ultimate aim is to increase our knowledge of the coping skills needed to achieve academic and vocational competence, so that future policies and practices in vocational as well as general education can be wisely designed. A three-stage investigation defines the procedure being used: (1 ) A study of the vocational goals and the problem-solving behavior ("coping style” ) of children who are competent and children who are not, plus a battery of achievement tests will be given to upper-lower-class boys and girls at ages 10 and 14, with a sample of middle-class children for comparison, both from urban zones. (2 ) A study of occupational values, and the coping styles preferred by the children’s teachers, and by parents and adults representing appropriate occupations. (3 ) The development of an assessment battery for measuring problem-solving skills, and cross-validation of this battery with a second sample of children. Outcomes will include reports on the place of the concept of work, and the coping styles. A clearer and more powerful theory with a higher degree of interpretation and prediction is anticipated as an outcome, explaining the widely varying range existing in amount of occupational effort and effectiveness found among lower- class youth— and also among middle-class youth. Personality factors such as aggressiveness, mastery of anxiety, interpersonal attitudes and attitudes toward authority will be tested for their contribution to work competence, and their place in occupational theory will thus be clarified. By the end of the study, it is expected that some specific recommendations can be made for the improvement of pre-vocational education in the several participating countries.